A new Laubieriellus species (Annelida, Spionidae) from Western Australia - Erickson, Ricky-Lee; Wilson, Robin S. (Zootaxa, 2018)
A new annelid species within the Prionospio- complex (Spionidae), Laubieriellus cacatua sp. nov., is described from material collected from the continental slope off the western margin of Australia. Laubieriellus cacatua sp. nov. is distinguished by having dorsal crests from chaetigers 6 to 11 and ventral crests on chaetigers 2 to 11. Neuropodial hooded hooks are present from chaetiger 10, with 2 pairs of apical teeth above the main tooth. Ventral sabre chaetae are present from chaetiger 10. This is the first record of Laubieriellus in Australia.